A computational fluid dynamics approach to improve multiphase flow measurement in a vertically installed venturi-based multiphase flowmeter - Zhan, Mengke (Nanyang Technological University, 2023)
Multiphase flowmeters (MPFMs) have been widely used in the production monitoring of upstream oil and gas wells with co-produced water. An MPFM generally consists of phase fraction and velocity (hence flow rate) measurements. Real-time in-line interpretation of liquid properties is also important for multiphase flow measurements; for example, many phase fraction measurement principles have a dependency on characteristics of water salinity. Despite the advantages of being able to perform continuous, inline, real-time oil-gas-water flow rate measurement without fluids separation, several challenges have been identified to further improve MPFM performance. Some of the challenges include difficulties to (i) improve the design parameters of upstream piping of vertically-installed MPFMs to establish flow homogeneity in order to maintain measurement accuracy and minimize manufacturing cost and carbon footprint, (ii) to identify a near-wall liquid-rich and water-liquid-ratio (WLR) representative location suitable for salinity and WLR measurement, and (iii) to scale multiphase flows with different fluid properties and flow conditions for generalities of the flow model. This study uses a computational fluids dynamics (CFD) approach, particularly the Eulerian-Eulerian multiphase framework with various models on interphase forces, to address the challenges in a vertically installed Venturi-based MPFM downstream a horizontal blind-tee. The simulation results are verified against experimental data collected at SLB and National University of Singapore (NUS) multiphase flow facilities.